The Reaction of the LQ45 Stock Market Listed on the Indonesia Stock Exchange to the Results of the Presidential and Vice Presidential Elections and the Factors Influencing Them - Alifah Nur Hanifati; Augustina Kurniasih (Indonesian Journal of Business Analytics, 2025)
The capital market plays an important role in the global economy as an indicator of economic stability and as a means of raising funds through investment. This study aims to examine the reaction of the Indonesian capital market to the announcement of the 2024 presidential and vice-presidential election results released by the General Elections Commission on March 20, 2024, as well as the factors influencing this reaction. The research focuses on companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX). This study employs two approaches: event study and causality. The event study is conducted to determine whether there is a capital market reaction by observing abnormal return (AR) and abnormal trading volume activity (ATVA) within an 11-day event window, covering 5 days before the event, the event day itself, and 5 days after the event. Meanwhile, the causality approach is used to explore the factors affecting AR and ATVA by examining the influence of Return on Equity (ROE) and firm size on the observed AR and ATVA. The findings indicate that the event did not generate significant abnormal return (AR) or abnormal trading volume activity (ATVA) during the 11-day period. Furthermore, profitability did not have a significant effect on either AR or ATVA. In contrast, firm size significantly influenced AR and ATVA, albeit in different directions. Firm size had a positive and significant effect on AR, but a negative and significant effect on ATVA.